The Concept of a Noble and a Perfect Person in Religious Philosophy - Sarsengali, B.; Shagyrbai, A. (Eurasian Journal of Religious Studies, 2022)
The formation of a noble and perfect person is the basis of social development. The ideas of nobility and perfection have evolved historically alongside human development. In the era of modern global processes and the fall of values, the concept of a noble and perfect person in religious philosophy does not lose its relevance. This article’s goal is to make clear the significance and essential characteristics of a noble and perfect person in religious philosophy. This article is based on the findings of numerous scientists who have investigated the issues raised by these concepts. The significance of comprehending the idea of a noble and perfect person from a theoretical standpoint is discussed in the article. We shall address each of these subjects in turn. First of all, we define the characteristics of a noble person and the role of Confucianism in defining the concept. The study revealed that a noble person should be an independent, moral, and unique individual. The primary features of a perfect person are then defined. It has been established that the perfect person is exemplary and distinguishable by ideality. Comparative analysis was used to study the scientific literature and produce the results. A descriptive approach was used to emphasize content analysis as well as systemic and historical research techniques. The article’s authors got to the conclusion that there are differences between what is meant by a noble person and what is meant by a perfect person.Key words: noble person, perfect person, being, humanity, Sufism.
Keywords: Noble Person; Perfect Person; Being; Humanity; Sufism